Relation Between Mean Platelet Volume and Severity of Atherosclerosis in Patients With Acute Coronary Syndromes. (February 2013) - Murat, Sani Namik; Duran, Mustafa; Kalay, Nihat; Gunebakmaz, Ozgur; Akpek, Mahmut; Doger, Cihan; Elcik, Deniz; Ocak, Ayse; Vatankulu, Mehmet Akif; Turfan, Murat; Kasapkara, Haci Ahmet; Akin, Fatih; et al.
Platelets play a central role in the pathophysiology of coronary artery disease (CAD). Increased mean platelet volume (MPV) is an indicator of platelet function and associated with poor clinical outcome in patients with acute coronary syndrome (ACS). We evaluated the relationship between MPV and severity of CAD in patients with ACS. A total of 395 patients with ACS were included. Severity of CAD was assessed with the Gensini and Syntax scores. High levels of MPV were associated with the Gensini and Syntax scores, number of diseased vessels (>50%), number of critical lesions (>50% and >70%), and noncritical lesions. After multivariate analysis, high levels of MPV were independent predictors of multivessel CAD together with age. In patients with ACS, high MPV levels were associated with severity of CAD. It is possible that MPV can be a helpful marker in patients with CAD for the severity of coronary atherosclerosis.